In “the zone”: The role of evolving skill and transitional workload on motivation and realized performance in operational tasks - Bendoly, Elliot; Prietula, Mike (International journal of operations & production management, 2008)
This paper examines how training specific to a given operational task, and subsequent experiential learning, can heighten skill and hence shift the level of workload at which individuals are most productively motivated. To analyze these effects, a laboratory experiment was used involving a vehicle routing application and 156 managers exposed to a 2 × 3 complete treatment design. Both multi-period objective in-task data and subjective self reports are collected to tap into skill levels, actions and behavioral variables of interest. In the absence of additional workload challenges, the paper finds that increases in skill may in fact significantly limit and in some cases actually degrade overall motivation, as well as objective performance. Limitations potentially stem from specific operationalizations of the factors studied as well as selectivity of the subject pool and the context (vehicle routing task). The implications of the skill-challenge-motivation dynamics observed have direct repercussions for existing management models in which training and experience are viewed as having strictly monotonic benefits to performance. The implications also go far to promote more informed models of worker behavior in operations modeling that otherwise view performance as static or monotonically increasing based on experience.